Volatiles of Taxus baccata L. as Attractants in Control of a Destructive Insect Pest Bactrocera cucurbitae Coquillett - Gupta, R. C.; Singh, A. K.; Fotedar, R. L.; Gahalain, S. S. (Indian Forester, 2009)
No abstract